2020
DOI: 10.3389/fnins.2020.608688
|View full text |Cite
|
Sign up to set email alerts
|

Brain Functional Interaction of Acupuncture Effects in Diarrhea-Dominant Irritable Bowel Syndrome

Abstract: Acupuncture is a traditional Chinese medicine treatment that has widely been used to modulate gastrointestinal dysfunction caused by irritable bowel syndrome (IBS) and to alleviate the resulting pain. Recent studies have shown that gastrointestinal dysfunction caused by IBS is associated with dysregulation of the brain's central and peripheral nervous system, while functional magnetic resonance imaging (fMRI) helps explore functional abnormality of the brain. However, previous studies rarely used fMRI to study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…A previous study evaluated functional connectivity using bilateral hippocampus regions, and the results showed that brain activity differed in the hippocampus, insula, temporo-sphenoid lobe, and occipital lobe in IBS-D patients with acupuncture treatment ( Geng et al, 2021 ). Additionally, increased degrees in the right middle occipital gyrus, and the clustering coefficients and local efficiency in the left superior occipital gyrus were also revealed in IBS-D patients with acupuncture treatment ( Ma et al, 2020 ).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A previous study evaluated functional connectivity using bilateral hippocampus regions, and the results showed that brain activity differed in the hippocampus, insula, temporo-sphenoid lobe, and occipital lobe in IBS-D patients with acupuncture treatment ( Geng et al, 2021 ). Additionally, increased degrees in the right middle occipital gyrus, and the clustering coefficients and local efficiency in the left superior occipital gyrus were also revealed in IBS-D patients with acupuncture treatment ( Ma et al, 2020 ).…”
Section: Discussionmentioning
confidence: 96%
“…Diarrhea-predominant irritable bowel syndrome patients received acupuncture treatment for 6 weeks, which has previously been reported to be effective for IBS-D patients ( Ma et al, 2020 ; Pei et al, 2020 ). Acupuncture at Baihui (GV20), Yintang (GV29), Taichong (LR3), Zusanli (ST36), Sanyinjiao (SP6), Tianshu (ST25), and Shangjuxu (ST37) acupoints were conducted by the same professional acupuncturist with more than 2 years of clinical experience.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of acupuncture analgesia has been proven in previous studies, and numerous clinical researches have explored the central mechanisms of acupuncture analgesia through neuroimaging techniques. 28 , 29 Our search revealed that no bibliometric analysis of fMRI studies on acupuncture analgesia was found. Therefore, understanding the current status of fMRI studies on acupuncture analgesia on a global scale is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies indicate that moxibustion could affect intestinal microbes [30,31], visceral hypersensitivity [31,32], the brain-gut axis [14,16], gastrointestinal function [33]. Other studies showed the moxibustion or acupuncture have bene t effect for IBS-D by regulating the neuroendocrine system [34], the immune system [35], and other factors.…”
Section: Discussionmentioning
confidence: 99%